O registro polêmico no hipergênero X: a Pandemia da Covid-19 - Falcão, Maria Dayanne Sampaio (2024)
The objective of this research is to analyze the polemical discourse about the Covid-19 pandemic in Brazil, in tweets posted between March 2020 and December 2021. In order to contribute to Dominique Maingueneau's theoretical-methodological apparatus, in the field of study of technodiscursive analysis. To achieve this objective, we investigated the enunciative dimension, the behavior of the generic scene of the register and outlined the positions constructed in the semantic dimension of the Polemical discourse on platform in Dominique Maingueneau's theoretical-methodological apparatus on controversial registration (including its enunciative, generic and semantic dimensions) and the web (digital and hypergenre scenography). Furthermore, we make small forays into digital discourse, in the view of Marie-Anne Paveau. The choice of the corpus considered the outline of 4 phases of the controversy over the Covid-19 pandemic in Brazil, which occurred in X, from March 2020 to December 2021, making a total of 22 tweets, 14 of them posted by political profiles with party affiliation linked to the extreme right and 8 by politicians from parties considered to be left-wing. After describing and interpreting the polemical discourse on X, we delve deeper into the analysis of the three dimensions of the record about the pandemic in tweets, highlighting the changes that the web causes in each of them. Due to the weakening of generic and encompassing scenes and the protagonism of scenography on the web, there is a destabilization in the traditional logic of the discursive field/genre/text. Consequently, promoting changes in the construction and maintenance of discursive identities mobilized during the Covid-19 pandemic. The resources available in the hypergenre X (such as 'threads', hashtags, 'videos, screenshots, images, links...') facilitated the construction of verbal and digital scenographies, which in turn created new ways to polemicize, discredit opponents, and argue in a polemical debate (such as the transformation of the reading logic of the 'third party' one aims to convince, by including videos or links in the tweet modules, thus providing new ways to lend credibility to positions). Consequently, in the semantic dimension of the register, we understand that these new forms of polemicizing and arguing... have transformed and refined the defense of positions involved in the controversy surrounding the Covid-19 pandemic in Brazil.